Evaluation of Current and Former Teleradiology Systems in Africa: A Review - Brandon Ewing; David Holmes (Ubiquity Press, 2022)
Background: Teleradiology has grown tremendously across the globe, providing significant benefits to both patients and physicians. In the late 1990s, South Africa sought to lead teleradiology adoption efforts by creating a national telemedicine system through a structured and phased approach. Although initial reports of the system's effectiveness were encouraging, the present status of this project, as well as comparable efforts in surrounding developing countries, has remained uncertain. Objective: To explore the status of teleradiology adoption in Africa, identify existing barriers to adoption, and explore potential solutions to the most commonly identified barriers. Methods: A narrative literature review was conducted to find articles that discussed current and past teleradiology systems in Africa. Each item was evaluated for relevance separately based on specified inclusion and exclusion criteria and was used to field further articles if relevant to the topic, even if not found in the initial search. The search began with articles published after January 1995 and included articles through December 2021. Findings: Although teleradiology systems in Africa has shown to have a benefit in improving patient outcomes, current implementation remains limited due to feasibility projects with no singular picture archiving and communication system (PACS) being utilized at the time of writing. Conclusions: Although teleradiology has significant potential and can benefit the developing countries in Africa, further expansion, in terms of both complexity and adoption rates, remains hindered by infrastructure development, clinician and technologist support, and general sociopolitical factors.